2010
DOI: 10.5491/shaw.2010.1.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Interleukin-8 and Tumor Necrosis Factor-alpha in Coal Workers' Pneumoconiosis: One-year Follow-up Study

Abstract: ObjectivesVarious cytokines induced by inhalation of coal dust may mediate inflammation and lead to tissue damage or fibrosis, such as coal workers' pneumoconiosis (CWP).MethodsTo investigate the relevance of serum cytokines in CWP, the levels of serum interleukin-8 (IL-8) and tumor necrosis factor-alpha (TNF-α) as CWP biomarkers in 110 retired coal miners (22 controls and 88 CWP subjects) were related to cross sectional findings and 1-year progressive changes of the pneumoconiosis. Progressive changes of CWP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…Similar results observed J.S. Lee et al, 2010: average values of TNF-α were significantly higher in subjects with FEV1 <80% compared to those in FEV1> 80% (23). The absence of significant differences in the spirometric parameters may be due to the fact that we studied clinically healthy people without registered respiratory diseases or functional deficits and abnormalities in spirometric testing.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results observed J.S. Lee et al, 2010: average values of TNF-α were significantly higher in subjects with FEV1 <80% compared to those in FEV1> 80% (23). The absence of significant differences in the spirometric parameters may be due to the fact that we studied clinically healthy people without registered respiratory diseases or functional deficits and abnormalities in spirometric testing.…”
Section: Resultssupporting
confidence: 77%
“…According to J.S. Lee et al, 2010, considerable release of TNF-α in subjects with the stage 0/1 ILO compared to controls supports the hypothesis for the crucial role of TNF-α in the pathogenesis of coal pneumoconiosis (24). TNF-α has been reported as a biomarker for progressive pneumoconiosis with levels correlating to the severity of the disease (25,26), i.e.…”
Section: Resultsmentioning
confidence: 75%
“…3 This exposure can promote a local and/or systemic inflammatory process, resulting in the production of inflammatory mediators; these mediators have been implicated in the etiology of silicosis, which include interleukin (IL)-1b, IL-6, IL-8, IL-13, IL-18, tumor necrosis factor (TNF)-a, soluble receptors of TNF-a, (sTNFR1 and sTNFR2), CCL-3 and CCL-24. [4][5][6][7][8][9][10] The diagnosis of silicosis is made by chest radiograph abnormalities that show the typical pattern of nodules and scars, together with the clinical and occupational history of the patient. 11 As silicosis is an irreversible disease, treatments can only relieve symptoms and minimize the decline of lung function.…”
mentioning
confidence: 99%
“…Levels of IL-8 were reportedly elevated in the supernatants of spontaneous or dust-stimulated monocytes isolated from peripheral blood and sera from non-progressing CWP patients8 ) . We previously found that serum levels of IL-8 were related to the presence of CWP, but were not related to the progression of CWP6 ) . In the present study, although no difference between study groups was identified, serum IL-8 levels tended to increase in association with CWP progression ( p =0.056) and ILO category (β=0.191, p =0.050).…”
Section: Discussionmentioning
confidence: 94%
“…Serum cytokines such as tumor necrosis factor-alpha (TNF-α)6, 7 ) , Interleukin-8 (IL-8)6, 8 ) , transforming growth factor-beta 1 (TGF-β1)9, 10 ) , and monocyte chemotactic protein-1 (MCP-1)11 ) have been considered as biomarkers for development or progression of CWP. Although evidence obtained from a various studies on the increased production of these cytokines following exposure crystalline silica or coal mine dust in macrophage and fibroblasts, only a limited number of human validation studies were reported in the literature1, 6 ) . These reports suggest the importance of serum cytokines in the CWP, however there are not lots of studied reports about the in vivo relevance of predictive discrimination between the levels of cytokines and progression of CWP.…”
Section: Introductionmentioning
confidence: 99%